High-strength carbon / ceramic brake disc with ceramic functional layer

The development of a high-strength carbon/ceramic brake disc with a ceramic functional layer addresses mechanical weaknesses and wear issues in conventional brake discs, resulting in improved strength, friction, and longevity for use in diverse vehicular applications.

JP2025507648AActive Publication Date: 2025-03-21XIAN CHAOMA SCI TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024549632
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-02-13
Filing Date
2023-05-26
Publication Date
2025-03-21
Estimated Expiration
2043-05-26

AI Technical Summary

Technical Problem

Conventional carbon/ceramic brake discs suffer from mechanical weakness, susceptibility to cracking, high wear rates, and short service life due to issues like oxidation of carbon fibers, uneven silicon distribution, and poor bonding strength of coatings.

Method used

A high-strength carbon/ceramic brake disc is developed with a ceramic functional layer produced by in situ reaction. This involves creating a carbon/carbon green body with a dual carbon matrix, where pyrolytic carbon protects carbon fibers from silicon liquid erosion, and a ceramic precursor paste is used to form a strong, adjustable ceramic layer.

Benefits of technology

The solution achieves a brake disc with enhanced mechanical strength, improved friction coefficient, reduced wear rate, and extended service life, capable of withstanding extreme braking conditions in various vehicles, including high-performance racing cars and heavy trucks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025507648000001_ABST
    Figure 2025507648000001_ABST
Patent Text Reader

Abstract

The present invention relates to a high-strength carbon / ceramic brake disc with a ceramic functional layer, which belongs to the technical field of vehicle brake parts. First, a carbon / carbon green body with a binary carbon matrix is ​​graphitized at high temperature, and then the carbon / carbon green body with a binary carbon matrix is ​​graphitized by liquid silicon infiltration reaction to produce a carbon / ceramic brake disc green body, and then a ceramic precursor paste is reacted in situ on the surface of the carbon / ceramic brake disc green body to form a ceramic functional layer, thereby obtaining the brake disc. The carbon / carbon green body with a binary carbon matrix can effectively protect the carbon fiber from the erosion by silicon liquid and reduce the proportion of residual silicon, and the ceramic functional layer formed by the in situ reaction has good binding force with the matrix and can be adjusted in thickness. The brake disc has the characteristics of high mechanical strength, high friction coefficient, low wear rate, excellent oxidation resistance, and long life, and has great future application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a high-strength carbon / ceramic brake disc with a ceramic functional layer, which belongs to the technical field of vehicle brake components. [Background technology]

[0002] Carbon / ceramic composite material is a composite material of carbon fiber reinforced carbon and silicon carbide ceramic matrix, which first appeared in the 1980s as a thermostructural material. It is a new high-temperature structural material and functional material with low density, good oxidation resistance, corrosion resistance, excellent high-temperature mechanical properties and thermophysical properties, and can withstand use at 1650℃. As a brake material, carbon / ceramic composite material has the advantages of wear resistance, high-temperature resistance, low density, large heat capacity, stable wet friction properties, and high-temperature friction coefficient that does not decay, making it the ideal brake material for new generation automobiles, high-speed trains, aircraft, tanks, etc.

[0003] German Patent DE 19727585 A1 discloses a combination of chopped fiber reinforced C / SiC ceramic brake disc, which is made by pressing chopped carbon fiber into a shape and then ceramicizing it, and a brake lining made of sintered metal material or non-organic adhesive material having a ceramic adhesive phase and metal particles. Chinese Patent CN113548902 A discloses a method for producing a carbon fiber reinforced silicon carbide brake disc, which comprises first heat treating chopped carbon fiber, then uniformly mixing chopped carbon fiber of various lengths with resin and additives, then pressing into a mold press, decomposing at high temperature under a protective atmosphere of nitrogen gas or inert gas, and finally infiltrating silicon in a vacuum infiltration furnace to obtain a carbon fiber reinforced silicon carbide brake disc. The carbon / ceramic brake disc produced by the above method has insufficient mechanical strength and is prone to cracking when hit by a hard object during use.

[0004] US Patent US7445095 "Braking system having a composite-material brake disc" discloses a combination of a carbon / ceramic brake disc with a friction layer and a composite brake pad, which has a friction coefficient of 0.4 to 0.48 and excellent friction characteristics. The surface friction layer contains a large amount of chopped carbon fibers, and when the temperature of the friction surface of the brake disc rises rapidly during braking, the carbon fibers oxidize at high temperatures and lose strength, resulting in an increased wear rate of the brake disc and a shortened service life.

[0005] Chinese patent CN105565839 A discloses a method for producing a carbon / ceramic brake material and a method for producing a carbon / ceramic brake disc. The mixture is obtained by adding ceramic powder to a phenolic resin solution, and the mixture is impregnated into a carbon fiber green body and carbonized to obtain a porous carbon / carbon-ceramic powder composite material, which is machined and then silicon infiltrated in a vacuum furnace to obtain a carbon / ceramic brake disc. There are problems in that the porous carbon / carbon-ceramic powder composite material is difficult to machine, the surface protection of the reinforcing carbon fiber is insufficient, and silicon erodes and damages the fiber during silicon infiltration, resulting in a lack of mechanical strength of the brake disc.

[0006] Chinese patent CN111892416 A discloses a method for producing carbon / ceramic brake materials, which comprises placing a low-density carbon / carbon green body in a silicon powder impregnated slurry, drying the impregnated carbon / carbon green body after completion of the impregnation, and then feeding the silicon powder impregnated carbon / carbon green body into a siliconization furnace, so that the silicon powder in the carbon green body and the carbon deposited on the surface of the green body are melted and chemically reacted in situ at high temperature to form a SiC ceramic phase. The silicon powder in the carbon / carbon green body after impregnation with the silicon powder impregnated slurry is concentrated in the outer layer, and the content of silicon powder gradually decreases from the inside to the outside, so that the brake disc material after ceramicization is non-uniform, there is an excessive amount of silicon remaining in the outer layer, and the content of SiC ceramic in the inner layer is excessively low, which affects the brake performance.

[0007] Chinese patent CN113277869 A discloses a carbon / ceramic brake disc with wear-resistant and oxidation-resistant coating and its manufacturing method, which is prepared by brushing a wear-resistant slurry containing 60% SiC particles into a groove pre-drilled on a carbon / carbon green body, and then coating the carbon / carbon composite disc body by using a deposition silicon infiltration process, where the silicon powder is not in contact with the carbon / carbon composite disc body, and the distance between the silicon powder and the carbon / carbon composite disc body is more than 100 mm. The coating introduced by the deposition process is thin and cannot play a long-term wear-resistant role, and only plays an anti-oxidation role, and a high proportion of SiC particles in the slurry are not generated by in-situ reaction, and have a weak bond with the matrix, which is easily dropped off during the friction process, and cannot form a stable friction film on the friction surface, so the wear rate of the brake disc and dual brake pad is relatively high.

[0008] Chinese patent CN108299002 A discloses a manufacturing process for C / C-SiC ventilated brake disc with silicon carbide friction functional layer, which involves reacting silicon vapor with carbon / carbon green body by trichloromethylsilane (CH3SiCl3) vapor phase silicon infiltration method to produce silicon carbide, obtaining a carbon / ceramic composite brake disc green body, and then depositing a layer of pure silicon carbide on the surface of the carbon / ceramic brake disc green body by CVI process to form a friction functional layer. Carbon / ceramic brake discs manufactured by this method have high raw material costs, long manufacturing period, and poor cost performance of brake disc products.

[0009] Chinese patent CN110131343 A discloses a method for manufacturing an automobile brake disc, which first adopts a one-piece press molding process to manufacture an automobile brake pair preform, then uses a polyazosilane solution and a polycarbosilane solution as a ceramic precursor, obtains a ceramic matrix through repeated impregnation and high-temperature decomposition, and finally manufactures a carbon fiber reinforced carbon / ceramic composite material. This method has low manufacturing efficiency, high cost, and high difficulty in industrial application. Summary of the Invention [Problem to be solved by the invention]

[0010] In response to the problems existing in the conventional brake disc, the present invention provides a high-strength carbon / ceramic brake disc with a ceramic functional layer, which is prepared by introducing pyrolytic carbon coated on carbon fiber and resin carbon or pitch carbon filled with pores into a carbon fiber preform to form a carbon / carbon green body with a binary carbon matrix, and then reacting with resin carbon or pitch carbon preferentially to generate SiC during the liquid silicon infiltration process. The pyrolytic carbon effectively protects the carbon fiber from erosion by the silicon liquid, thereby increasing the strength retention rate of the carbon fiber and ensuring the high mechanical strength of the brake disc. The ceramic functional layer formed by the in-situ reaction has good bonding strength with the matrix, is adjustable in thickness, and can effectively achieve the comprehensive functions of wear resistance, oxidation resistance, and improved friction coefficient. As a result, the brake disc has the characteristics of high mechanical strength, high friction coefficient, low wear rate, good oxidation resistance, and long service life, and can be used not only in conventional automobiles, airplanes, and high-speed trains, but also in the extreme braking environment requirements of high-performance racing cars, large trucks, and tanks. [Means for solving the problem]

[0011] The object of the present invention is achieved by the following technical solutions:

[0012] A high strength carbon / ceramic brake disc with a ceramic functional layer, First, a carbon / carbon green body with a dual carbon matrix is ​​graphitized at high temperature, and then the graphitized carbon / carbon green body with a dual carbon matrix is ​​manufactured into a carbon / ceramic brake disc green body by liquid silicon infiltration reaction; then, a ceramic precursor paste is reacted in situ on the surface of the carbon / ceramic brake disc green body to form a ceramic functional layer, thereby obtaining the brake disc; The carbon / carbon green body of the dual carbon matrix is ​​manufactured by first coating the carbon fiber surface of the carbon fiber preform with pyrolytic carbon using a chemical vapor deposition process, and then filling the pores of the carbon fiber preform with resin carbon or pitch carbon using an impregnation carbonization process. The carbon fiber preform is formed by needle punching carbon fibers and carbon mesh tires, and has a density of 0.4 to 0.6 g / cm. 3 The density after coating with pyrolytic carbon is 0.8 to 1.3 g / cm 3 After filling with resin carbon or pitch carbon, the density remains at 1.0-1.5g / cm 3 and accordingly, the density of the carbon / ceramic brake disc green body increased to 1.9-2.4g / cm. 3 and The ceramic precursor paste is a mixture of a thermosetting resin, polymethylsilane, and silicon powder in a mass ratio of 30:(15-40):(30-55). The thermosetting resin is preferably a phenol resin, an epoxy resin, or a furfural acetone resin. After mixing the thermosetting resin, the polymethylsilane, and the silicon powder, the mixture is preferably stirred and mixed for 0.5 to 2 hours.

[0013] The carbon fiber preform is manufactured by the steps of spreading carbon fiber, pre-needle punching with a carbon mesh tire to produce a carbon fiber-carbon mesh tire unit layer, laying a plurality of carbon fiber-carbon mesh tire unit layers flat layer by layer in a flat needle punch machine, and successively needle punching the layers to form a 2.5D carbon fiber flat felt, which is then cut according to the size of the brake disc to obtain a carbon fiber preform; The carbon fiber is preferably 12-48K carbon fiber, where K represents the number of tows in a thousand. In the needle punching process of the carbon fiber-carbon mesh tire unit layer, the lamination direction is adjusted to alternately laminate and needle punch at 0° / 90°, and the needle punch density is 16-30 needles / cm. 2 Let us assume that.

[0014] The steps for preparing the carbon / carbon green body of the binary carbon matrix are specifically as follows: Density: 0.4~0.6g / cm 3 The carbon fiber preform is placed in a chemical vapor deposition furnace, and a carbon source gas and a dilution gas are introduced to perform chemical vapor deposition under conditions of a high temperature of 900 to 1200 °C and a vacuum degree of 500 to 4000 Pa, to form pyrolytic carbon covering the carbon fibers on the surface of the carbon fiber preform, and the density is 0.80 to 1.3 g / cm. 3 to obtain a carbon / carbon green body with a unit carbon matrix of The carbon source gas is natural gas or propylene (C3H6), the diluent gas is nitrogen gas (N2) or hydrogen (H2), and the volume ratio of the carbon source gas to the diluent gas is (1 to 3):1; The carbon / carbon green body of the unit carbon matrix is ​​placed in a vacuum-pressure impregnation and hardening furnace, heated until the impregnating agent is softened, and the carbon / carbon green body of the unit carbon matrix is ​​impregnated using a vacuum method or a pressure method, the impregnating agent is inserted into the internal pores of the carbon / carbon green body of the unit carbon matrix, the remaining impregnating agent is discharged, and then the temperature is raised to 170-220°C and kept at that temperature for 1-4 hours to harden the impregnating agent in the carbon / carbon green body of the unit carbon matrix, and then the carbonization furnace is placed in the carbonization temperature controlled at 850-1000°C and the carbonization time controlled at 2-6 hours, and the density is 1.0-1.5g / cm. 3 to obtain a carbon / carbon green body with a binary carbon matrix of The impregnating agent is a furfural acetone resin, a phenolic resin or a pitch, and the pressure inside the furnace during pressurized impregnation is 1.5 MPa or more.

[0015] The step of graphitizing the carbon / carbon green body of the binary carbon matrix at high temperature specifically includes: The carbon / carbon green body of the dual carbon matrix is ​​placed in a high-temperature treatment furnace, nitrogen gas or inert gas is introduced, and the temperature is raised to 1800-2400°C under a protective atmosphere, and the temperature is kept for 1-6 hours to complete the high-temperature graphitization treatment of the carbon / carbon green body of the dual carbon matrix.

[0016] The step of producing a carbon / ceramic brake disc green body specifically includes the steps of: First, the carbon / carbon green body of the graphitized binary carbon matrix is ​​mechanically processed according to the drawing of the final product to produce a molded body, then the molded body is placed in a graphite crucible, and the silicon powder is added according to the filling amount calculated from the volume of the final product. After filling is completed, the graphite crucible is placed in a high-temperature furnace, heated to 1600-2000 °C, kept warm for 1-4 h, and the vacuum degree is controlled to 200-2000 Pa to melt the solid silicon material into silicon liquid, which enters the pores of the molded body due to the capillary effect, and Si and C come into contact with each other and undergo a chemical reaction at the silicon carbon contact surface to produce SiC, with a density of 1.9-2.4 g / cm 3 A carbon / ceramic brake disc green body is obtained.

[0017] Silicon powder is spread evenly on the bottom of the crucible, and 5 to 8 spacers made of porous silicon carbide material are placed in the silicon powder to support the molded body and prevent the silicon powder from coming into contact with the molded body.

[0018] The step of producing a ceramic functional layer on the surface of the carbon / ceramic brake disc green body by in-situ reaction specifically includes: The prepared ceramic precursor paste is applied to the surface of the carbon / ceramic brake disc green body with a brush, or the carbon / ceramic brake disc green body is impregnated with the prepared ceramic precursor paste, and then dried and placed in a high-temperature furnace, heated to 1600 to 2000°C, and kept at that temperature for 1 to 3 hours to form a ceramic functional layer on the surface of the carbon / ceramic brake disc green body. After that, the required metal parts are polished and the required metal parts are attached to obtain a high-strength carbon / ceramic brake disc with a ceramic functional layer.

[0019] The ceramic functional layer preferably has a thickness of 0.5 to 3 mm. Effect of the Invention

[0020] The beneficial effects are as follows: (1) In the present invention, a carbon / carbon green with a binary carbon matrix is ​​adopted, and pyrolytic carbon coating the carbon fiber and resin carbon or pitch carbon filling the pores are introduced into the carbon fiber preform. During the subsequent liquid silicon infiltration process, silicon reacts preferentially with resin carbon or pitch carbon to generate SiC. The pyrolytic carbon coating on the carbon fiber surface can effectively protect the carbon fiber from erosion by the silicon liquid, and maximize the strength and toughness of the carbon fiber, ensuring the high mechanical strength of the brake disc. (2) In the present invention, when resin carbon or pitch carbon is introduced into the carbon fiber preform, the introduced impregnating agent is carbonized and then shrunk to form pores, thereby forming a flow path for the subsequent silicon liquid to enter, storing a carbon source for the silicon-carbon reaction after the silicon liquid enters the pores, effectively reducing the proportion of residual silicon, and controlling the mass ratio of residual silicon to within 5%. Since the melting point of Si (about 1420°C) is much lower than the melting point of SiC (about 2700°C), the present invention can greatly improve the high-temperature stability of the brake disc. (3) In the present invention, in order to fully utilize the purpose of the pyrolytic carbon covering the carbon fiber to protect the carbon fiber from erosion by silicon, the thickness of the introduced pyrolytic carbon is about 1 to 3 μm, that is, the density is 0.4 to 0.6 g / cm. 3 The carbon fiber preform has a density of 0.8 to 1.3 g / cm 3 In order to fully react the resin carbon / pitch carbon with the liquid silicon, the weight ratio of the introduced resin carbon / pitch carbon is 25-35%, i.e. 1.0-1.5 g / cm 3 By scientifically blending the content of pyrolytic carbon and resin carbon / pitch carbon in the dual matrix carbon, the proportion of residual silicon can be effectively reduced, the strength retention rate of carbon fiber can be greatly improved, and the mechanical performance of carbon / ceramic brake discs can be improved by 10-20%. (4) In the present invention, when pyrolytic carbon is introduced into the carbon fiber preform, the volume ratio of the carbon source gas to the dilution gas, the deposition temperature, the degree of vacuum, and other conditions are controlled to control the microstructure of the pyrolytic carbon formed, forming pyrolytic carbon with a coarse layer structure and avoiding pyrolytic carbon with an isotropic layer structure. This is because the coarse layer pyrolytic carbon has a higher friction coefficient, is easier to graphitize, and is easier to open holes than isotropic pyrolytic carbon, which is advantageous for the later ceramicization reaction and can maintain stable tribological performance of the brake disc. (5) In the present invention, a ceramic functional layer with good bonding strength with the matrix and adjustable thickness is manufactured on the surface of the brake disc by in-situ reaction. In order to better bring out the advantages of SiC ceramics in terms of high friction coefficient, high hardness and oxidation resistance, the content of SiC in the manufactured ceramic functional layer is made to be more than 92% by mass through scientific design of the formula of the ceramic functional layer, which is much higher than the content of SiC in the brake disc body (40-70% by mass), effectively improving the friction coefficient, wear resistance and oxidation resistance of the brake disc, and significantly extending the service life of the brake disc. (6) The brake disc according to the present invention has the characteristics of high mechanical strength, high friction coefficient, low wear rate, excellent oxidation resistance, and long service life. It can be used not only in conventional automobiles, airplanes, and high-speed trains, but also in high-performance racing cars, large trucks, tanks, and other vehicles with extreme braking conditions. [Brief description of the drawings]

[0021] [Figure 1] 1 is a scanning electron microscope (SEM) image of the coarse-layered pyrolytic carbon deposited on the surface of the carbon fiber preform in step (2) of Example 1. [Diagram 2] 1 is a scanning electron microscope (SEM) image of isotropic pyrolytic carbon deposited on the surface of the carbon fiber preform in step (2) of Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The invention will now be further described with reference to certain embodiments, in which the processes are conventional processes unless otherwise specified, and the raw materials are available from public commercial sources unless otherwise specified.

[0023] Example 1 (1) Using SYT49S-12K carbon fiber manufactured by China Fu Shenying Company, the carbon fiber and the carbon mesh tire are pre-needle punched to produce a carbon fiber-carbon mesh tire unit layer. A flat needle punch machine is used to lay multiple carbon fiber-carbon mesh tire unit layers flat and sequentially needle punch them, so that they are alternately stacked at 0° / 90° in the planar direction, and the needle punch density in the thickness direction is 16 needles / cm 2 The 2.5D carbon fiber flat felt is then cut to the size of the brake disc, with an outer diameter of 390mm, a thickness of 38mm, and a density of 0.4g / cm 3 Thus, a carbon fiber preform was obtained. (2) The carbon fiber preform produced in step (1) is placed in a chemical vapor deposition furnace, the temperature in the furnace is increased to 900°C, and when the degree of vacuum in the furnace reaches a stabilized pressure of 500 Pa, carbon source gas C3H6 and dilution gas N2 are introduced in a volume ratio of 1:1, and chemical vapor deposition is performed for 150 hours, resulting in a density of 0.91 g / cm3. 3 A carbon / carbon green body with a unit carbon matrix was obtained, and when observed under a polarizing microscope, it was found that what was deposited on the surface of the carbon fiber preform was coarse-layered pyrolytic carbon, and its micromorphology was as shown in Figure 1. (3) The carbon / carbon green body of the unit carbon matrix produced in step (2) is placed in a vacuum-pressurized impregnation and curing furnace, and phenolic resin is used as an impregnating agent. The phenolic resin is heated and pressurized to 1.5 MPa in the vacuum-pressurized impregnation and curing furnace to allow the phenolic resin to enter the pores inside the product. After the residual phenolic resin is discharged under pressure, the temperature inside the furnace is slowly raised to 180°C to cause a curing reaction. After 3 hours of curing reaction, the product is removed and placed in a carbonization furnace to be carbonized at a carbonization temperature of 850°C for 5 hours, resulting in a density of 1.18 g / cm. 3Carbon / carbon green with a binary carbon matrix was prepared. (4) The carbon / carbon green body with dual carbon matrix prepared in step (3) was placed into a high-temperature treatment furnace, protected by introducing nitrogen gas, and slowly heated to 1800°C and kept at that temperature for 6 hours to complete the high-temperature graphitization treatment of the carbon / carbon green body with dual carbon matrix. (5) The carbon / carbon green body of the binary carbon matrix graphitized in step (4) was mechanically processed according to the final product drawings to process the inner diameter, outer diameter, and thickness as required, and to drill vent holes to produce a compact. (6) 2500 g of silicon powder is laid flat on the bottom of the graphite crucible, and five spacers made of porous silicon carbide material are placed in the silicon powder. The molded body produced in step (5) is placed on the spacers to prevent the silicon powder from contacting the molded body. Then, the graphite crucible is placed in a high-temperature furnace, the vacuum degree is controlled to 200 Pa, the temperature is slowly increased to 1600 °C, and the temperature is kept for 4 h. The silicon powder is melted into silicon liquid, and then the silicon liquid is introduced into the holes of the molded body by the capillary effect. Si and C react to produce SiC, with a density of 2.26 g / cm. 3 Carbon / ceramic brake green bodies were obtained. (7) Phenol resin, polymethylsilane, and silicon powder were mixed in a mass ratio of 30:15:55, and mixed by mechanical stirring for 0.5 hours to prepare a ceramic precursor paste. The prepared ceramic precursor paste was brushed onto the surface of the carbon / ceramic brake disc green body produced in step (6), and then dried and cured. The body was then placed in a high-temperature furnace, slowly heated to 1600°C, and kept at that temperature for 3 hours to form a ceramic functional layer with a thickness of 0.5 mm on the surface of the carbon / ceramic brake disc green body. (8) The carbon / ceramic brake disc green body having a ceramic functional layer on its surface produced in step (7) was polished, and the required metal parts were attached to obtain a high-strength carbon / ceramic brake disc having a ceramic functional layer.

[0024] Example 2 (1) Using SYT49S-12K carbon fiber manufactured by Sinofu Shenying Company, the carbon fiber and the carbon mesh tire are pre-needle punched to produce a carbon fiber-carbon mesh tire unit layer. A flat needle punch machine is used to lay multiple carbon fiber-carbon mesh tire unit layers flat and sequentially needle punch them, so that they are alternately stacked at 0° / 90° in the planar direction, and the needle punch density in the thickness direction is 30 needles / cm 2 The 2.5D carbon fiber flat felt is then cut to the size of the brake disc, with an outer diameter of 390mm, a thickness of 38mm, and a density of 0.6g / cm 3 Thus, a carbon fiber preform was obtained. (2) The carbon fiber preform produced in step (1) is placed in a chemical vapor deposition furnace, the temperature in the furnace is raised to 1200°C, and when the degree of vacuum in the furnace reaches a stabilized pressure of 4000 Pa, CH4 as a carbon source gas and H2 as a dilution gas are introduced in a volume ratio of 3:1, and chemical vapor deposition is performed for 200 hours, resulting in a density of 1.22 g / cm3. 3 A carbon / carbon green body having a unit carbon matrix was obtained, and when observed under a polarizing microscope, it was found that the material deposited on the surface of the carbon fiber preform was coarse-layered pyrolytic carbon. (3) The carbon / carbon green body of the unit carbon matrix produced in step (2) is placed in a vacuum-pressurized impregnation and curing furnace, and furfural acetone resin is used as an impregnating agent. The furfural acetone resin is heated and pressurized to 2.5 MPa in the vacuum-pressurized impregnation and curing furnace to allow the furfural acetone resin to enter the pores inside the product. After the residual furfural acetone resin is discharged under pressure, the temperature inside the furnace is slowly raised to 220°C to carry out a curing reaction. After 2 hours of curing reaction, the product is taken out and placed in a carbonization furnace to be carbonized at a carbonization temperature of 1000°C for 4 hours, resulting in a density of 1.45 g / cm. 3 Carbon / carbon green with a binary carbon matrix was prepared. (4) The carbon / carbon green body with dual carbon matrix prepared in step (3) was placed into a high-temperature treatment furnace, protected by introducing nitrogen gas, and slowly heated to 2200°C and kept at that temperature for 1 hour to complete the high-temperature graphitization treatment of the carbon / carbon green body with dual carbon matrix. (5) The carbon / carbon green body of the binary carbon matrix graphitized in step (4) was mechanically processed according to the final product drawing to obtain the required inner diameter, outer diameter, and thickness, and to form a molded body by drilling vent holes. (6) 2500 g of silicon powder is laid flat on the bottom of the graphite crucible, and eight spacers made of porous silicon carbide material are placed in the silicon powder. The molded body produced in step (5) is placed on the spacers to prevent the silicon powder from contacting the molded body. Then, the graphite crucible is placed in a high-temperature furnace, the vacuum degree is controlled to 2000 Pa, the temperature is slowly raised to 2000 °C, and the temperature is kept for 1 h. The silicon powder is melted into silicon liquid, and then the silicon liquid is introduced into the holes of the molded body by the capillary effect. Si and C react to produce SiC, with a density of 2.09 g / cm. 3 Carbon / ceramic brake green bodies were obtained. (7) Furfural acetone resin, polymethylsilane, and silicon powder were mixed in a mass ratio of 30:28:42, and mixed by mechanical stirring for 2 hours to prepare a ceramic precursor paste. The prepared ceramic precursor paste was brushed onto the surface of the carbon / ceramic brake disc green body produced in step (6), and then dried and cured. The body was then placed in a high-temperature furnace, slowly heated to 2000°C, and kept at that temperature for 1 hour to form a ceramic functional layer with a thickness of 3 mm on the surface of the carbon / ceramic brake disc green body. (8) The carbon / ceramic brake disc green body having a ceramic functional layer on its surface produced in step (7) was polished, and the required metal parts were attached to obtain a high-strength carbon / ceramic brake disc having a ceramic functional layer.

[0025] Comparative Example 1 (1) Adopting SYT49S-24K carbon fiber manufactured by China Fu Shenying Co., Ltd., nonwoven fabric and carbon mesh tires are alternately layered and needle punched, the angle between the directions of adjacent nonwoven fabrics is 0° / 90°, and the needle punch density in the thickness direction is 20 needles / cm 2 The sheet is then needle-punched layer by layer and cut to an outer diameter of 390 mm, a thickness of 40 mm, and a density of 0.50 g / cm. 3 A 2.5D preform was manufactured. (2) A chemical vapor deposition process was performed similarly to step (2) of Example 2 to obtain a 1.28 g / cm 3 A carbon / carbon green body with a unit carbon matrix was obtained. (3) The carbon / carbon green body of the unit carbon matrix produced in step (2) was subjected to high temperature treatment in the same manner as in step (4) of Example 2. (4) The carbon / carbon green body of the unit carbon matrix treated at high temperature in step (3) was mechanically processed according to the drawing of the final product to process the inner diameter, outer diameter, and thickness as required, and to drill ventilation holes to obtain a molded body. (5) The green body produced in step (4) was subjected to a ceramic treatment in the same manner as in step (6) of Example 2, and the volume density was accordingly reduced to 2.05 g / cm 3 Carbon / ceramic brake disc green bodies were obtained. (6) The carbon / ceramic brake disc green body produced in step (5) was polished and required metal parts were attached to obtain a carbon / ceramic brake disc having no ceramic functional layer.

[0026] Comparative Example 2 (1) Adopting SYT49S-24K carbon fiber manufactured by China Fu Shenying Co., Ltd., nonwoven fabric and carbon mesh tires are alternately laminated and needle punched, the angle between the directions of adjacent nonwoven fabrics is 0° / 90°, and the needle punch density in the thickness direction is 20 needles / cm 2 The sheet is then needle-punched layer by layer and cut to an outer diameter of 390 mm, thickness of 40 mm, and density of 0.50 g / cm. 3 A 2.5D preform was manufactured. (2) The carbon fiber preform produced in step (1) was subjected to a resin impregnation carbonization treatment in the same manner as in step (3) of Example 2. The resin impregnation carbonization treatment was repeated four times to obtain a carbon fiber preform having a density of 1.26 g / cm3, in which the matrix carbon is resin carbon. 3 A carbon / carbon green body with a unit carbon matrix was obtained. (3) The carbon / carbon green body of the unit carbon matrix produced in step (2) was subjected to high temperature treatment in the same manner as in step (4) of Example 2. (4) The carbon / carbon green body of the unit carbon matrix treated at high temperature in step (3) was mechanically processed according to the drawing of the final product to process the inner diameter, outer diameter, and thickness as required, and to drill ventilation holes to produce a compact. (5) The green body produced in step (4) was subjected to a ceramic treatment in the same manner as in step (6) of Example 2, and the volume density was accordingly reduced to 2.07 g / cm 3 Carbon / ceramic brake disc green bodies were obtained. (6) The carbon / ceramic brake disc green body produced in step (5) was polished and required metal parts were attached to obtain a carbon / ceramic brake disc having no ceramic functional layer.

[0027] Comparative Example 3 (1) Adopting SYT49S-24K carbon fiber manufactured by China Fu Shenying Co., Ltd., nonwoven fabric and carbon mesh tires are alternately laminated and needle punched, the angle between the directions of adjacent nonwoven fabrics is 0° / 90°, and the needle punch density in the thickness direction is 20 needles / cm 2 The sheet is then needle-punched layer by layer and cut to an outer diameter of 390 mm, a thickness of 40 mm, and a density of 0.60 g / cm. 3 A 2.5D preform was manufactured. (2) The carbon fiber preform produced in step (1) was subjected to chemical vapor deposition for 300 h in the same manner as in step (2) of Example 2, and the density was 1.49 g / cm 3 A carbon / carbon green body with a unit carbon matrix was obtained. (3) The carbon / carbon green body of the unit carbon matrix produced in step (2) was impregnated and carbonized in the same manner as in step (3) of Example 2 to obtain a carbon green body with a density of 1.70 g / cm. 3 Carbon / carbon green bodies with a binary carbon matrix were prepared. (4) The carbon / carbon green body with a binary carbon matrix prepared in step (3) was subjected to a high temperature treatment in the same manner as in step (4) of Example 2. (5) The carbon / carbon green body of the binary carbon matrix treated at high temperature in step (4) was mechanically processed according to the drawing of the final product, and the inner diameter, outer diameter, and thickness were processed as specified, and ventilation holes were drilled to produce a compact. (6) The green body produced in step (4) was subjected to a ceramic treatment in the same manner as in step (6) of Example 2, and the volume density was accordingly 1.89 g / cm 3 Carbon / ceramic brake disc green bodies were obtained. (7) The carbon / ceramic brake disc green body produced in step (6) was polished and required metal parts were attached to obtain a carbon / ceramic brake disc having no ceramic functional layer.

[0028] Comparative Example 4 (1) Adopting SYT49S-24K carbon fiber manufactured by China Fu Shenying Co., Ltd., nonwoven fabric and carbon mesh tires are alternately laminated and needle punched, the angle between the directions of adjacent nonwoven fabrics is 0° / 90°, and the needle punch density in the thickness direction is 20 needles / cm 2 The sheet is then needle-punched layer by layer and cut to an outer diameter of 390 mm, a thickness of 40 mm, and a density of 0.60 g / cm. 3 A 2.5D preform was manufactured. (2) The carbon fiber preform produced in step (1) is placed in a chemical vapor deposition furnace, the temperature in the furnace is raised to 1100°C, and when the degree of vacuum in the furnace reaches a stabilized pressure of 2000 Pa, CH4 as a carbon source gas and H2 as a dilution gas are introduced so that the volume ratio of CH4 to H2 is 1:2. Chemical vapor deposition is performed for 200 hours, and the density is 1.02 g / cm. 3A carbon / carbon green body having the above unit carbon matrix was obtained, and when observed under a polarizing microscope, the produced pyrolytic carbon had an isotropic structure, as shown in FIG. (3) The carbon / carbon green body of the unit carbon matrix produced in step (2) is placed in a vacuum-pressurized impregnation and curing furnace, and furfural acetone resin is used as an impregnating agent. The furfural acetone resin is heated and pressurized to 2.5 MPa in the vacuum-pressurized impregnation and curing furnace to be introduced into the pores inside the product. The residual furfural acetone resin is discharged under pressure, and the temperature inside the furnace is slowly raised to 220°C to carry out a curing reaction. After 2 hours of curing reaction, the product is taken out and placed in a carbonization furnace to be carbonized at a carbonization temperature of 1000°C for 4 hours, resulting in a density of 1.24 g / cm. 3 Carbon / carbon green bodies with a binary carbon matrix were prepared. (4) The carbon / carbon green body with a binary carbon matrix prepared in step (3) was subjected to a high temperature treatment in the same manner as in step (4) of Example 2. (5) The high temperature treated dual carbon matrix carbon / carbon green body produced in step (4) was mechanically processed according to the final product drawing to machine the inner diameter, outer diameter, and thickness as required, and to drill vent holes to produce a compact. (6) The green body produced in step (4) was subjected to a ceramic treatment in the same manner as in step (6) of Example 2, and the volume density was accordingly 1.78 g / cm 3 Carbon / ceramic brake disc green bodies were obtained. (7) The carbon / ceramic brake disc green body produced in step (5) was polished and required metal parts were attached to obtain a carbon / ceramic brake disc having no ceramic functional layer.

[0029] In order to further study and evaluate the mechanical properties and friction and wear properties of the carbon / ceramic brake discs manufactured in the examples and comparative examples, the carbon / ceramic brake discs manufactured in the examples and comparative examples were combined with imported brake pads designed specifically for carbon / ceramic discs, and ground bench tests were conducted using a LINK3000 bench tester in accordance with the SAEJ2522-AK Master test standard. The strength and test results are shown in Table 1 below.

[0030] [Table 1]

[0031] In Comparative Example 1, which is a carbon / ceramic brake disc containing only unit carbon matrix (pyrolytic carbon), there is no resin carbon to consume the Si source, so the mass ratio of residual silicon is 15.3%, which reduces the mechanical properties and adversely affects the high-temperature friction properties. In Comparative Example 2, which is a carbon / ceramic brake disc containing only unit carbon matrix (resin carbon), there is no protection by pyrolytic carbon on the carbon fiber surface, which causes reactive erosion of the carbon fiber by liquid silicon, and the bending strength of the carbon / ceramic brake disc is greatly reduced. In Comparative Example 3, which contains a binary carbon matrix, the ratio of the two is unbalanced and the content of matrix carbon is too high, which results in a low hole opening rate of the green body and poor silicon infiltration flow path, and therefore the content of SiC ceramic in the carbon / ceramic brake disc is low, the product has low density, and low compressive strength. In Comparative Example 4, the process parameters are not reasonable, so the coarse layer structure is not formed as the microstructure of the pyrolytic carbon, and the main component is isotropic carbon, which is unfavorable for high-temperature graphitization and drilling. The silicon infiltration flow path is poor, so the content of SiC ceramic in the carbon / ceramic brake disc is low, the density of the product is low, and the performance is poor. In all of Comparative Examples 1 to 4, the ceramic functional layer is not formed, so the friction coefficient is generally lower than that of the Examples, and the wear rate is generally higher than that of the Examples. From the test results in the above table, it can be seen that the high-strength carbon / ceramic brake disc with a ceramic functional layer manufactured by the present invention can maximize the strength and toughness of the carbon fiber by introducing a binary matrix carbon (pyrolytic carbon and resin carbon / pitch carbon), effectively reduce the proportion of residual silicon, and greatly improve the mechanical strength of the material. The ceramic functional layer introduced by in-situ reaction can greatly improve the friction coefficient and reduce the wear rate.

[0032] As mentioned above, the above is only a preferred embodiment of the present invention, and does not limit the protection scope of the present invention. Any amendments, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention should be included within the protection scope of the present invention.

[0033] (Additional Note) (Appendix 1) A high strength carbon / ceramic brake disc with a ceramic functional layer, First, a carbon / carbon green body with a dual carbon matrix is ​​graphitized at high temperature, and then the graphitized carbon / carbon green body with a dual carbon matrix is ​​manufactured into a carbon / ceramic brake disc green body by liquid silicon infiltration reaction; then, a ceramic precursor paste is reacted in situ on the surface of the carbon / ceramic brake disc green body to form a ceramic functional layer, thereby obtaining the brake disc; The carbon / carbon green body of the dual carbon matrix is ​​manufactured by first coating the carbon fiber surface of the carbon fiber preform with pyrolytic carbon using a chemical vapor deposition process, and then filling the pores of the carbon fiber preform with resin carbon or pitch carbon using an impregnation carbonization process. The carbon fiber preform is formed by needle punching carbon fibers and carbon mesh tires, and has a density of 0.4 to 0.6 g / cm. 3 The density after coating with pyrolytic carbon is 0.8 to 1.3 g / cm 3 After filling with resin carbon or pitch carbon, the density remains at 1.0-1.5g / cm 3 and accordingly, the density of the carbon / ceramic brake disc green body increased to 1.9-2.4g / cm. 3 and The ceramic precursor paste is a mixture of thermosetting resin, polymethylsilane, and silicon powder in a mass ratio of 30:(15-40):(30-55). A high-strength carbon / ceramic brake disc with a ceramic functional layer, characterized in that

[0034] (Appendix 2) The carbon fiber preform is manufactured by the steps of spreading carbon fiber and pre-needle punching with a carbon mesh tire to produce a carbon fiber-carbon mesh tire unit layer, laying a plurality of carbon fiber-carbon mesh tire unit layers flat layer by layer in a flat needle punch machine, and successively needle punching the layers to form a 2.5D carbon fiber flat felt, which is then cut according to the size of the brake disc to obtain a carbon fiber preform; A high-strength carbon / ceramic brake disc having a ceramic functional layer according to claim 1.

[0035] (Appendix 3) In the process of needle punching the carbon fiber-carbon mesh tire unit layer, the stacking direction is adjusted to alternately stack and needle punch at 0° / 90°, and the needle punch density is set to 16~30 needles / cm 2 The carbon fiber used is 12~48K carbon fiber. A high-strength carbon / ceramic brake disc having a ceramic functional layer according to claim 2.

[0036] (Appendix 4) The steps for preparing the carbon / carbon green body of the binary carbon matrix are specifically as follows: Density: 0.4~0.6g / cm 3 The carbon fiber preform is placed in a chemical vapor deposition furnace, and a carbon source gas and a dilution gas are introduced to perform chemical vapor deposition under conditions of a high temperature of 900 to 1200 °C and a vacuum degree of 500 to 4000 Pa, to form pyrolytic carbon covering the carbon fibers on the surface of the carbon fiber preform, and the density is 0.80 to 1.3 g / cm. 3 to obtain a carbon / carbon green body with a unit carbon matrix of The carbon / carbon green body of the unit carbon matrix is ​​placed in a vacuum-pressure impregnation and hardening furnace, heated until the impregnating agent is softened, and the carbon / carbon green body of the unit carbon matrix is ​​impregnated using a vacuum method or a pressure method, the impregnating agent is inserted into the internal pores of the carbon / carbon green body of the unit carbon matrix, the remaining impregnating agent is discharged, and then the temperature is raised to 170-220°C and kept at that temperature for 1-4 hours to harden the impregnating agent in the carbon / carbon green body of the unit carbon matrix, and then the carbonization furnace is placed in the carbonization temperature controlled at 850-1000°C and the carbonization time controlled at 2-6 hours, and the density is 1.0-1.5g / cm. 3 to obtain a carbon / carbon green body with a binary carbon matrix of The carbon source gas is natural gas or propylene, the diluent gas is nitrogen gas or hydrogen, the volume ratio of the carbon source gas to the diluent gas is (1-3):1, the impregnating agent is furfural acetone resin, phenolic resin or pitch, and the pressure in the furnace during pressurized impregnation is 1.5 MPa or more; 4. A high-strength carbon / ceramic brake disc comprising the ceramic functional layer according to any one of claims 1 to 3.

[0037] (Appendix 5) The step of graphitizing the carbon / carbon green body of the binary carbon matrix at high temperature specifically includes: The carbon / carbon green body of the dual carbon matrix is ​​placed into a high-temperature treatment furnace, and nitrogen gas or inert gas is introduced into the furnace to heat the body to 1800-2400°C under a protective atmosphere, and the temperature is kept for 1-6 hours to complete the high-temperature graphitization of the carbon / carbon green body of the dual carbon matrix. A high-strength carbon / ceramic brake disc having a ceramic functional layer according to claim 1.

[0038] (Appendix 6) The step of producing a carbon / ceramic brake disc green body specifically includes the steps of: First, the graphitized carbon / carbon green body of the binary carbon matrix is ​​mechanically processed according to the drawing of the final product to produce a molded body, and then the molded body is placed in a graphite crucible, and the filling amount is calculated from the volume of the final product and silicon powder is added. After filling is completed, the graphite crucible is placed in a high-temperature furnace, heated to 1600-2000 °C, kept at that temperature for 1-4 h, and the degree of vacuum is controlled to 200-2000 Pa, and the density is set to 1.9-2.4 g / cm. 3 Obtaining the carbon / ceramic brake disc green body, A high-strength carbon / ceramic brake disc having a ceramic functional layer according to claim 1.

[0039] (Appendix 7) Silicon powder is laid flat on the bottom of the crucible, and 5 to 8 spacers made of porous silicon carbide material are placed in the silicon powder to support the molded body and prevent the silicon powder from contacting the molded body. 7. A high-strength carbon / ceramic brake disc comprising a ceramic functional layer according to claim 6.

[0040] (Appendix 8) The thermosetting resin in the ceramic precursor paste is a phenolic resin, an epoxy resin or a furfural acetone resin; A high-strength carbon / ceramic brake disc having a ceramic functional layer according to claim 1.

[0041] (Appendix 9) The step of producing a ceramic functional layer on the surface of the carbon / ceramic brake disc green body by in-situ reaction specifically includes: The prepared ceramic precursor paste is applied to the surface of the carbon / ceramic brake disc green body by a brush, or the carbon / ceramic brake disc green body is impregnated with the prepared ceramic precursor paste, and then dried and placed in a high-temperature furnace, heated to 1600-2000°C, and kept at that temperature for 1-3 hours to form a ceramic functional layer on the surface of the carbon / ceramic brake disc green body. A high-strength carbon / ceramic brake disc having a ceramic functional layer according to claim 1.

[0042] (Appendix 10) The thickness of the ceramic functional layer is 0.5~3mm. 10. A high-strength carbon / ceramic brake disc comprising a ceramic functional layer according to claim 1, 8 or 9.

Claims

1. A high strength carbon / ceramic brake disc with a ceramic functional layer, First, a carbon / carbon green body with a dual carbon matrix is ​​graphitized at high temperature, and then the graphitized carbon / carbon green body with a dual carbon matrix is ​​manufactured into a carbon / ceramic brake disc green body by liquid silicon infiltration reaction, and then a ceramic precursor paste is reacted in situ on the surface of the carbon / ceramic brake disc green body to form a ceramic functional layer, thereby obtaining the brake disc; The carbon / carbon green body of the dual carbon matrix is ​​manufactured by first coating the carbon fiber surface of the carbon fiber preform with pyrolytic carbon using a chemical vapor deposition process, and then filling the pores of the carbon fiber preform with resin carbon or pitch carbon using an impregnation carbonization process. The carbon fiber preform is formed by needle punching carbon fibers and a carbon mesh tire, and has a density of 0.4 to 0.6 g / cm. 3 and the density after coating with pyrolytic carbon is 0.8 to 1.3 g / cm 3 After filling with resin carbon or pitch carbon, the density remains at 1.0 to 1.5 g / cm 3 and correspondingly, the density of the carbon / ceramic brake disc green body increased to 1.9-2.4 g / cm 3 and The ceramic precursor paste is a mixture of thermosetting resin, polymethylsilane, and silicon powder in a mass ratio of 30:(15-40):(30-55). A high-strength carbon / ceramic brake disc having a ceramic functional layer.

2. The carbon fiber preform is manufactured by the steps of spreading carbon fiber and pre-needle punching with a carbon mesh tire to produce a carbon fiber-carbon mesh tire unit layer, laying a plurality of carbon fiber-carbon mesh tire unit layers flat layer by layer in a flat needle punch machine, and successively needle punching the layers to form a 2.5D carbon fiber flat felt, which is then cut according to the size of the brake disc to obtain a carbon fiber preform; 2. A high-strength carbon / ceramic brake disc provided with a ceramic functional layer according to claim 1.

3. In the process of needle punching the carbon fiber-carbon mesh tire unit layer, the lamination direction is adjusted to alternately laminate and needle punch at 0° / 90°, and the needle punch density is set to 16 to 30 needles / cm 2 and using 12 to 48K carbon fiber as the carbon fiber.

3. A high-strength carbon / ceramic brake disc provided with a ceramic functional layer according to claim 2.

4. The steps for producing a carbon / carbon green body with a dual carbon matrix are specifically as follows: Density: 0.4 to 0.6 g / cm 3 The carbon fiber preform is placed in a chemical vapor deposition furnace, and a carbon source gas and a dilution gas are introduced under conditions of a high temperature of 900 to 1200°C and a vacuum degree of 500 to 4000 Pa to perform chemical vapor deposition, thereby forming pyrolytic carbon covering the carbon fibers on the surface of the carbon fiber preform, and the density is 0.80 to 1.3 g / cm. 3 to obtain a carbon / carbon green body having a unit carbon matrix of The carbon / carbon green body of the unit carbon matrix is ​​placed in a vacuum-pressurized impregnation and curing furnace, heated until the impregnating agent is softened, and the carbon / carbon green body of the unit carbon matrix is ​​impregnated using a vacuum method or a pressure method, the impregnating agent is inserted into the internal pores of the carbon / carbon green body of the unit carbon matrix, the remaining impregnating agent is discharged, and then the temperature is raised to 170-220°C and kept at that temperature for 1-4 hours to cause the impregnating agent in the carbon / carbon green body of the unit carbon matrix to undergo a curing reaction, and then the carbonization furnace is placed therein, and the carbonization temperature is controlled to 850-1000°C, the carbonization time is controlled to 2-6 hours, and the density is 1.0-1.5 g / cm. 3 to obtain a carbon / carbon green body having a binary carbon matrix of The carbon source gas is natural gas or propylene, the diluent gas is nitrogen gas or hydrogen, the volume ratio of the carbon source gas to the diluent gas is (1-3):1, the impregnating agent is furfural acetone resin, phenolic resin or pitch, and the pressure inside the furnace during pressurized impregnation is 1.5 MPa or more; A high-strength carbon / ceramic brake disc comprising a ceramic functional layer according to any one of claims 1 to 3.

5. The step of graphitizing the carbon / carbon green body of the binary carbon matrix at high temperature specifically includes the steps of: The carbon / carbon green body of the dual carbon matrix is ​​placed in a high-temperature treatment furnace, and nitrogen gas or inert gas is introduced to heat the body to 1800-2400°C under a protective atmosphere, and the temperature is kept for 1-6 hours to complete the high-temperature graphitization treatment of the carbon / carbon green body of the dual carbon matrix.

2. A high-strength carbon / ceramic brake disc provided with a ceramic functional layer according to claim 1.

6. The steps of producing a carbon / ceramic brake disc green body are specifically: First, the graphitized carbon / carbon green body of the binary carbon matrix is ​​mechanically processed according to the drawing of the final product to produce a molded body, and then the molded body is placed in a graphite crucible, and the filling amount is calculated from the volume of the final product and silicon powder is added. After filling is completed, the graphite crucible is placed in a high-temperature furnace, heated to 1600-2000°C, and kept at that temperature for 1-4 h. The degree of vacuum is controlled to 200-2000 Pa, and the density is set to 1.9-2.4 g / cm. 3 obtaining a carbon / ceramic brake disc green body of 2. A high-strength carbon / ceramic brake disc provided with a ceramic functional layer according to claim 1.

7. Silicon powder is laid evenly on the bottom of the crucible, and 5 to 8 spacers made of porous silicon carbide material are placed in the silicon powder to support the molded body and prevent the silicon powder from contacting the molded body.

7. A high-strength carbon / ceramic brake disc with a ceramic functional layer according to claim 6.

8. The thermosetting resin in the ceramic precursor paste is a phenolic resin, an epoxy resin or a furfural acetone resin; 2. A high-strength carbon / ceramic brake disc provided with a ceramic functional layer according to claim 1.

9. The step of producing a ceramic functional layer on the surface of the carbon / ceramic brake disc green body by in-situ reaction specifically comprises: The prepared ceramic precursor paste is applied to the surface of the carbon / ceramic brake disc green body by a brush, or the carbon / ceramic brake disc green body is impregnated with the prepared ceramic precursor paste, and then dried and placed in a high-temperature furnace, heated to 1600 to 2000°C, and kept at that temperature for 1 to 3 hours, to form a ceramic functional layer on the surface of the carbon / ceramic brake disc green body.

2. A high-strength carbon / ceramic brake disc provided with a ceramic functional layer according to claim 1.

10. The thickness of the ceramic functional layer is 0.5 to 3 mm.

10. A high-strength carbon / ceramic brake disc provided with a ceramic functional layer according to claim 1, 8 or 9.

Citation Information

Patent Citations

  • Ceramic brake disk for use in high speed brake system, has friction layers made of silicon and silicon carbide, where part of silicon carbide and / or carbon components of layers and / or carrier body is encapsulated in envelope

    DE102009050025A1

  • Composite carbon / carbon-silicon carbide friction member and manufacturing method thereof

    JP2001505863A

  • Method for producing fiber preforms for manufacturing parts made of carbon / carbon-type composites incorporating ceramic particles and products obtained therefrom

    JP2008525295A

  • High temperature coatings

    US20220250996A1

  • CARBON-FIBER-REINFORCED SiC COMPOSITE MATERIAL AND SLIDE MEMBER

    WO2007004482A1